Attenuation of sound radiation in concrete structure through the reduction of mechanical vibration - HOLANDA,R. V. DE (2018)
Abstract The efficiency of sound irradiance in structure has direct relation with its vibratory movement. Dynamic vibration absorbers (DVAs) are a low cost viable option for reducing vibrations in passive structures. Secondary systems attached to the primary system (structure) in order to reduce vibration. In this work it was used an experimental modal analysis procedure (EMA) for vibratory responses through impulsive excitations to determine the natural frequencies and the location of points suitable for attachment of DVAs in a concrete beam. Later it was designed and built DVAs to reduce vibration in a frequency band where the response of the human auditory system is more sensitive. The best project configuration for DVAs was evaluated for sensitivity thereof with respect to the change of the loss factor of the viscoelastic material used. Obtained reduction of more than 36% over the considered frequency band and over 70% in the region of the resonance frequency in which the DVAs were tuned.